PELAKSANAAN PEMBELAJARAN KETERAMPILAN DESAIN GRAFIS BAGI MURID DISABILITAS RUNGU DI SLB NEGERI 1 LIMA KAUM - Andea Rozanti, Tasya; Taufan, Johandri; Efrina, Elsa; Zulpiani, Mardhatillah; Muspita, Rila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of graphic design skills instruction for students with deaf and hard of hearing (DHH) at SLB Negeri 1 Lima Kaum. The research method used was qualitative descriptive, with data collection techniques including observation, interviews, and document analysis. The subjects of this study consisted of the graphic design teacher, students with DHH disabilities, and the school principal. This study was analyzed using the Miles & Huberman model through the stages of data reduction, data presentation, and drawing conclusions, then its validity was tested through triangulation of sources and techniques. The research findings indicate that lesson plans are systematically developed by adapting the curriculum to students’ visual abilities. Instruction begins with the simplest materials and progresses to more complex ones. Instructional delivery emphasizes hands-on practice, visual demonstrations, and material repetition to address auditory communication barriers. Teachers’ pedagogical practices integrate Direct Instruction, Chunking, and Scaffolding methods, supported by digital tools such as CorelDraw and Canva. Evaluation is conducted continuously, based on both process and product. The primary challenges encountered include reversal errors (reversed writing), a characteristic of hearing impairment, and difficulties in long-term memory regarding tool symbols and their functions. The solutions implemented include structured repetition up to 5 times, specific technical cues for computer operations, and the preparation of substitute teachers. These findings underscore the importance of optimizing the vocational potential of students with hearing impairments, making them relevant as a reference for the development of skills programs at Special Education Schools in West Sumatra.